Sobre The Tapestry of Reason: An Inquiry into the Nature of Coherence and its Role in Legal Argument, de Amalia Amaya - Vega Gómez, Juan (Isonomía - Revista de teoría y filosofía del derecho, 2017)
En su libro The Tapestry of Reason: An Inquiry into the Nature of Coherence and its Role in Legal Argument,1 Amalia Amaya argumenta las ventajas de adoptar una postura coherentista en el derecho. Concretamente, su tesis principal es la siguiente...